Indonesia's trials and tribulations : the case of Abu Bakar Ba'asyir - Sulastri Osman (2012)
With hardliner Abu Bakar Ba’asyir once again in the spotlight facing multiple charges of terrorism, Indonesian authorities have to instil public confidence in its revised anti-terrorism laws to maintain credibility and stem religious extremism. An open and transparent trial has never been more crucial.